Efektivitas Penggunaan Media Pembelajaran Digital Safari Hura Terhadap Kemampuan Berpikir Simbolik Anak Kelompok A TK Amelia Jember - Fadea Putri Kalista Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study was motivated by the problem of children's symbolic thinking skills at Amelia Jember Kindergarten, which was marked by the low achievement of several indicators such as children were not yet able to recognize the concept of numbers, recognize letter symbols, and recognize number symbols. The factors that are factors in children's low symbolic thinking skills are interest and talent factors, this is because the learning process is still centered on the teacher and the low quality of media facilities in assisting the learning process, resulting in a lack of interest and attraction for children to actively participate in the learning process. This study aims to determine the effectiveness of the use of digital learning media safari hura on the symbolic thinking skills of children aged 4-5 years. The type of research used is an experiment with a One Group Pretest-Posttest Design. Research at Amelia Jember Kindergarten showed significant learning outcomes with an average pretest score of 56.25 and an average posttest score of 85.08. Children's symbolic thinking skills increased by 28.83 after being given treatment for 5 meetings. Based on the results of the study, it can be concluded that the use of digital learning media safari hura is effective in improving the symbolic thinking skills of children aged 4 5 years.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: Children Aged 4-5 Years; Symbolic Thinking; Interactive Powerpoint